الاختلاف في متعلق حروف الجر في القرآن الكريم وأثره في الوقف والابتداء - بوعافية, محمد الصالح; عطوات, كوثر (جامعة الوادي - University of Eloued, 2021)
أشباه الجمل الظرفية أو المتكونة من جارٍّ ومجرورٍ متعلَّق تتعلق به، سواء سبقها أو تقدمت عليه، وفي آيات القرآن الكريم مواطن كثيرة وردت فيها شبه الجملة من جار ومجرور اختلف العلماء في تحديد متعلقها، وقد نشأ عن هذا الاختلاف تغايرٌ في مواضع الوقف والابتداء. وهذه الدراسة تهدف إلى إبراز هذه الظاهرة من خلال حروف الجر: (من، وفي، والباء واللام، وعن، وعلى) ومتعلقاتها. For adverbial or prepositional sentences a concerning related to it whether previously or progressed. And in the verses of the Holy Quran verses many instances in which the concering of prepositional sentences is hardly determined by scientists. This study aims to highlight this phenomenon through arabic prepositions and their concerning.
Article
Keywords: حروف الجر- التعلُّق - القرآن الكريم - الوقف والابتداء; prepositions, concerning, Holy Quran, initiation, stopping